Selective Reduction in Microglia Density and Function in the White Matter of Colony-stimulating factor-1–Deficient Mice - Kondo, Yoichi (J Neurosci Res, 2009)
It is still debated whether microglia play a beneficial or harmful role in myelin disorders such as multiple sclerosis and leukodystrophies as well as in other pathological conditions of the central nervous system. The osteopetrotic (op/op) mouse has reduced numbers of cells of monocyte lineage as a result of an inactivating mutation in the colony stimulating factor-1 gene. To determine whether this mutant mouse might be used to study the role of microglia in myelin disorders, we quantified the number of microglia in the central nervous system of op/op mice and explored their ability to respond to brain injury created by a stab wound. Microglial density in the 2-month-old op/op mice was significantly decreased in the white matter tracts compared with the -ge matched wild-type controls (by 63.6% in the corpus callosum and 86.4% in the spinal dorsal column), whereas the decrease was less in the gray matter, cerebral cortex (24.0%). A similar decrease was seen at 7 months of age. Morphometric studies of spinal cord myelination showed that development of myelin was not affected in op/op mice. In response to a stab wound, the increase in the number of microglia/macrophages in op/op mice was significantly less pronounced than that in wild-type control. These findings demonstrate that this mutant is a valuable model in which to study roles of microglia/macrophages in the pathophysiology of myelin disorders.